![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. Vì \(\hept{\begin{cases}\left|x+\frac{1}{2}\right|\ge0\forall x\\\left|y-\frac{3}{4}\right|\ge0\forall y\\\left|z-1\right|\ge0\forall z\end{cases}}\)=> | x +\(\frac{1}{2}\)| + | y -\(\frac{3}{4}\)| + | z - 1 |\(\ge\)0\(\forall\)x ; y ; z
Dấu "=" xảy ra <=> \(\hept{\begin{cases}\left|x+\frac{1}{2}\right|=0\\\left|y-\frac{3}{4}\right|=0\\\left|z-1\right|=0\end{cases}}\)<=>\(\hept{\begin{cases}x=-\frac{1}{2}\\y=\frac{3}{4}\\z=1\end{cases}}\)
Vậy x = - 1/2 ; y = 3/4 ; z = 1
Câu b,c bạn làm tương tự nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
a)ta có xy=7*9=7*3*3
vậy x =9;21 , y=7;3
b) xy=-2*5
mà x<0<y
nên x=-2 ,y=5
c)x-y=5 hay x=y+5
\(\frac{y+5+4}{y-5}=\frac{4}{3}\Rightarrow3y+27=4y-20\Rightarrow y=47\Rightarrow x=52\)
|\(x\) - \(\dfrac{1}{2}\)|.|y.\(\dfrac{2}{3}\)|.|\(x^2\).\(x.z\)| = 0
⇒ \(\left[{}\begin{matrix}x-\dfrac{1}{2=0}\\y.\dfrac{2}{3}=0\\x=0\\z=0\end{matrix}\right.\)
⇒ \(\left[{}\begin{matrix}x=\dfrac{1}{2}\\y=0\\x=0\\z=0\end{matrix}\right.\)